Sustainable operations management - Mukherjee, Kampan 1956- (Boca Raton, FL CRC Press, 2024)
The proposed book includes concepts, methodologies, and practices for achieving sustainability in business operations. The underlying concept is explained from two perspectives - organizational level and policy level. In former, all principles, techniques, and decision-making issues relevant to, sustainability at unit level, management of product recovery processes, and sustainability at integrated level, are captured. Content on policy level perspective includes policies, norms, guidelines and regulatory measures both at global and national levels. Primary goal of this book is creation of an integrated and value rich platform for initiation and management of sustainable operations. Features: Comprehensive overview on environmental sustainability from the operations and supply chain perspective. Proposes an understandable and innovative viewpoint in explaining sustainable operations management comprehensively as managing operations sustainably at organizational level. Readers will learn the concepts, techniques and the core factors relating to managing operations keeping in view various dimensions of sustainability and the macro level guidelines, norms, regulatory measures etc in this context. Adds to knowledge on design, planning and management of sustainable operations including the specific management approaches. Includes summary and review questions at the end of each chapter. This book is aimed at graduate students and researchers in industrial, production, and mechanical engineering including operations management. It is also recommended as textbook for the courses like sustainable development, sustainable operations management, and environmental management"--
Includes bibliographical references and index.
Keywords: Decision making; Production management; Sustainability